The Erasmus+ mobility programme at the Lisbon School of Health Technology: characteristics and motivations of participants from 2009-2019 - Dolan, Ana (2022)
The Erasmus+ Mobility Programme (EMP) was established in 1987. It aims to promote both intercultural cooperation and communication and the development of higher education at a European level. The program has had over 4 million participants, but the rates of participation by Portuguese students are low. This is also the case for STEM students across the EU member states. Therefore, it is pertinent to analyze the profile of these students. The first EMP for Orthoptics and Vision Sciences (OVS) students at the Lisbon School of Health Technology (ESTeSL) took place in 2003. The Países de Língua Oficial Portuguesa Mobility Programme (PMP), mobility between ESTeSL and Portuguese-speaking African countries, began in 2016. Aims of the study: to characterize the participants in the EMP and PMP mobility programs between 2009/10 and 2019/20; to identify participants’ preferred fields of study; to emphasize the advantages of EMP and PMP for OVS students at ESTeSL according to students; to understand the students' motivations for selecting ESTeSL as their destination university; to determine the student’s satisfaction.